ADOLESCENT KNOWLEDGE AND AWARENESS ABOUT AIDS/HIV AND FACTORS AFFECTING THEM IN BANGLADESH - Rahman, M. Mizanur; Kabir, M.; Shahidullah, M. (Journal of Ayub Medical College Abbottabad, 2009)
Background: Adolescents are more vulnerable than adults of unplanned pregnancies, sexually transmitted diseases and HIV/AIDS. Among the adolescents, girls are more vulnerable to STDs including HIV/AIDS. Their knowledge about different diseases is very poor. This paper investigated adolescent's knowledge about sexually transmitted diseases including HIV/AIDS, its mode of transmission and ways of its prevention. Methods: Cross sectional study design was adopted for this study. A multistage cluster sampling technique was used to select the sample. Data on 3362 female adolescents irrespective of their marital status was analyzed. Results: The study found that a large proportion of adolescents were not aware about sexually transmitted diseases and AIDS. More than half ï€¨54.8ï€¥ï€© of the adolescents ever heard about AIDS respectively. On an average, about one tenth of them had better knowledge on AIDS in terms of mode of transmission and prevention. The multivariate logistic regression analysis revealed that adolescent age, years of schooling and knowledge on STDs appeared to be important predictors of the awareness about AIDS ï€¨p<0.05ï€©. Conclusions: Useful and fruitful media campaigns to educate the adolescents regarding the health consequences of STDs including HIV/AIDS and integrated approach is strongly suggested for creating knowledge and awareness to control the spread of HIV and AIDS among young people in Bangladesh. Keywords: Adolescent, Knowledge, Awareness, STDs, AIDS/HIV, Bangladesh